Evaluation of the influences of low dose polybrominated diphenyl ethers exposure on human early retinal development. (May 2022) - Li, Minghui; Zeng, Yuxiao; Ge, Lingling; Gong, Jing; Weng, Chuanhuang; Yang, Cao; Yang, Junling; Fang, Yajie; Li, Qiyou; Zou, Ting; Xu, Haiwei
Graphical abstract: Highlights: Human embryonic stem cell-derived retinal organoids for the toxic assessment. BDE-47 disrupted the development of neural retina. BDE-47 regulated retinal cell fate through gene transcription and metabolism. PBDE may disrupt human early embryonic retinal development. Abstract: Increasing evidence in animal models has suggested that polybrominated diphenyl ethers (PBDEs), a class of brominated flame retardants, can cause retinotoxicity. However, data on the influence of PBDE treatment on human retinal development are scarce due to the lack of appropriate models. In the present study, we report the utilization of human embryonic stem cell-derived retinal organoids (hESC-ROs) for toxicity assessment of the most common PBDE congener (BDE-47) during the early stages of retinal development. Exposure to BDE-47 decreased the thickness and area of the neural retina (NR) of hESC-ROs in a dose- and time-dependent manner. Abnormal retinal cell distributions, disordered NR structures, and neural rosette-like structures were found on hESC-ROs after low-level BDE-47 exposure. Moreover, BDE-47 exposure decreased cell proliferation, promoted cell apoptosis, and caused abnormal differentiation. Transcriptomic analysis demonstrated that differentially expressed genes, caused by BDE-47, were enriched in extracellular matrix organization. Metabolomic studies of hESC-ROs revealed significant changes in the metabolism of purine and glutathione after BDE-47 exposure for five weeks. This study clarifies the retinotoxicity of low-level BDE-47 treatment and highlights the powerfulness of the hESC-RO model, deepening our understanding of BDE-47-driven human early retina developmental toxicity.